Cyclical industries’ stock performance reaction during COVID-19: a systematic - Norhamiza Ishak,; Hanita Kadir @ Shahar,; Chia, Ricky Chee Jiun (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study explores the impact of COVID-19 on stock market reactions of cyclical and non-cyclical industries during the pandemic. This paper aims to provide a systematic literature review (SLR) of studies done on the effect of COVID-19 on stock price. The PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guided this study through an SLR within the month of October 2020. Under the PRISMA, the study was scrutinized through three process: 1) defining clear research questions that permit a systematic research, 2) identifying the inclusion and exclusion criteria, and 3) examining large databases of scientific literature in a defined time. A total of 18 out of 56 papers were identified and analysed to give better understanding of the pandemic’s effect on industry companies and the methodologies adopted in past studies. This paper analyses the major theme, namely cyclical industries impacted by COVID-19. The industries experiencing such value destructions include tourism, airlines, restaurants and transportation. The findings of this review are expected to have implications on investors, academicians and the public at large, particularly with regards to how unprecedented events such as COVID-19 can inflict economic damage.